Delayed memory effects after intense stress in Special Forces candidates: Exploring path processes between cortisol secretion and memory recall. (May 2013) - Taverniers, John; Taylor, Marcus K.; Smeets, Tom
<x xml:space="preserve">Abstract</x> The aim of this paper is twofold. First, it explores delayed effects of high endogenously evoked cortisol concentrations on visuo-spatial declarative memory. Subsequently, it applies multiple mediation (MM) analyses to reveal path processes between stress and cognitive performance in a sample of 24 male Special Forces (SF) candidates (mean age = 27.0 years, SD = 4.1). The SF candidates were randomly assigned to a control (n = 12) or an intense stress group (n = 12), and cortisol secretion for the intense stress condition was triggered by a brusque 60 min prisoner of war exercise. Stress exposure provoked robust increases in cortisol concentrations and a significant decline in immediate recall performance, measured with the Rey–Osterrieth Complex Figure (ROCF). The relative retrieval differences in regard to the ROCF persisted even after a recovery period of 24 h, as both groups showed similar levels of memory decline over 24 h. Next, the study applied a MM design that involved distribution-independent asymptotic and resampling strategies to extend traditional bivariate analyses. MM results showed that ROCF performance was mediated by increases in cortisol concentrations. Considering the studied variables, the current analysis was the first to provide statistical support for the generally accepted thesis that cortisol secretion in itself, rather than subjective strain or the experimental treatment, affects cognitive performance. The revelation of such path processes is important because it establishes process identification and may refine existing paradigms.